Grundy Number of Some Chordal Graphs - Nagarathinam, R.; Parvathi, N.; ., . (International Journal of Engineering and Technology, 2018)
For a given graph G and integer k, the Coloring problem is that of testing whether G has a k-coloring, that is, whether there exists a vertex mapping c : V â†’ {1, 2, . . .} such that c(u) 12Ã¢â€°Â "> c(v) for every edge uv âˆˆ E. For proper coloring, colors assigned must be minimum, but for Grundy coloring which should be maximum. In this instance, Grundy numbers of chordal graphs like Cartesian product of two path graphs, join of the path and complete graphs and the line graph of tadpole have been executedÂ